2007
DOI: 10.1021/jf0709193
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Trichothecene Toxins in an Arabidopsis thaliana Leaf Assay

Abstract: Many Fusarium species produce trichothecenes, sesquiterpene epoxides that differ in patterns of oxygenation and esterification at carbon positions C-3, C-4, C-7, C-8, and C-15. For the first comprehensive and quantitative comparison of the effects of oxygenation and esterification on trichothecene phytotoxicity, we tested 24 precursors, intermediates, and end products of the trichothecene biosynthetic pathway in an Arabidopsis thaliana detached leaf assay. At 100 microM, the highest concentration tested, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 27 publications
3
62
1
Order By: Relevance
“…However, the number and position of hydroxyl and acetyl ester groups on the trichothecene structure can also influence the mechanism of protein synthesis inhibition and relative toxicities within eukaryotic cells (32)(33)(34). In this regard, we found that the position of an acetyl ester group on either carbon 3 or 15 of DON (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…However, the number and position of hydroxyl and acetyl ester groups on the trichothecene structure can also influence the mechanism of protein synthesis inhibition and relative toxicities within eukaryotic cells (32)(33)(34). In this regard, we found that the position of an acetyl ester group on either carbon 3 or 15 of DON (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Tcin was isolated from Trichothecium roseum and prepared as described (12). DAS, T-2, and DON were prepared as described (41).…”
Section: Methodsmentioning
confidence: 99%
“…Trichoderma arundinaceum and T. brevicompactum also produce trichothecenes, sesquiterpenoid compounds which are harmful to plants and to the animals which consume contaminated food or feed stocks. Several studies on the structure-activity relationships of Fusarium trichothecene toxins in alga, plant, and animal models (5)(6)(7) indicate that certain Fusarium trichothecenes and intermediates have different toxic effects. Using an Arabidopsis leaf assay, Desjardins and coworkers found that toxicity varied Ͼ200-fold between different trichothecene compounds, while trichodiene (TD), a hydrocarbon precursor, was not phytotoxic (6).…”
mentioning
confidence: 99%